PENGARUH SISTEM PELACAKAN ONLINE DAN KETEPATAN WAKTU PENGIRIMAN TERHADAP KEPUASAN PELANGGAN - Kencana, Dadang Surya; Al Munir, Sipon; Mahardika, Yoga Pranaya (POLITEKNIK LP3I JAKARTA, 2025)
This study aims to determine the effect of the online tracking system and on-time delivery on customer satisfaction at PT Berkah Prima Gemilang, both partially and simultaneously. This type of research is descriptive quantitative. Primary data was obtained through distributing questionnaires to customers. The study was conducted at PT Berkah Prima Gemilang located in West Cikarang, Bekasi Regency, from January to June 2025. The operationalization of variables includes the Online Tracking System (X1), On-Time Delivery (X2), and Customer Satisfaction (Y), with evidence of validity and reliability through Pearson and Cronbach Alpha tests using SPSS software. The study population was 39 people and the sampling technique used a saturated sampling method. Data collection techniques were carried out with a closed questionnaire using a Likert scale. Data were analyzed using validity tests, reliability tests, multiple linear regression analysis, t-tests, F-tests, and coefficients of determination. The results showed that the online tracking system and on-time delivery, both partially and simultaneously, had a significant effect on customer satisfaction. The conclusion of this study is that improving the quality of the tracking system and on-time delivery can increase customer satisfaction. Suggestions for companies are to strengthen information systems and optimize on-time delivery to build better customer loyalty.